Links between Vitamin K, Ferroptosis and SARS-CoV-2 Infection - Jarosław Nuszkiewicz; Paweł Sutkowy; Marcin Wróblewski; Marta Pawłowska; Roland Wesołowski; Joanna Wróblewska; Alina Woźniak (MDPI AG, 2023)
Ferroptosis is a recently discovered form of programmed cell death. It is characterized by the accumulation of iron and lipid hydroperoxides in cells. Vitamin K is known to have antioxidant properties and plays a role in reducing oxidative stress, particularly in lipid cell membranes. Vitamin K reduces the level of reactive oxygen species by modulating the expression of antioxidant enzymes. Additionally, vitamin K decreases inflammation and potentially prevents ferroptosis. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection leading to coronavirus disease 2019 (COVID-19) is associated with oxidant-antioxidant imbalance. Studies have shown that intensified ferroptosis occurs in various tissues and cells affected by COVID-19. Vitamin K supplementation during SARS-CoV-2 infection may have a positive effect on reducing the severity of the disease. Preliminary research suggests that vitamin K may reduce lipid peroxidation and inhibit ferroptosis, potentially contributing to its therapeutic effects in COVID-19 patients. The links between ferroptosis, vitamin K, and SARS-CoV-2 infection require further investigation, particularly in the context of developing potential treatment strategies for COVID-19.